Author Correction: Radiative recombination of confined electrons at the MgZnO/ZnO heterojunction interface. Issue 1 (December 2017) - Choi, Sumin; Rogers, David; Sandana, Eric; Bove, Philippe; Teherani, Ferechteh; Nenstiel, Christian; Hoffmann, Axel; McClintock, Ryan; Razeghi, Manijeh; Look, David; Gentle, Angus; Phillips, Matthew; et al.
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.